Quantum key supply and dynamic adjustment strategies for power dispatch - Wei DENG; Zhuozhi YU; Yefeng ZHANG; Yalin CHEN; Yonghong MA (Dianxin kexue)
In order to ensure the transmission security of electric power dispatching service data,a quantum key supply and dynamic adjustment algorithm was provided.Firstly,the key application mode was determined according to the priority of different services,and the calculation method of the key pool capacity was also provided.Secondly,the quantum key dynamic adjustment algorithm was designed based on the key update frequency and application mode.Finally,the traffic model for the dispatching system was established,and the algorithm’s application performance for different scenarios was simulated within point-to-point/multipoint architectures.The test results show that the algorithm can realize the dynamic key adjustment in the selected adjustment period,and thus improves the security of the scheduling data transmissions.